Changing Patterns of Lymphoma in the Antiretroviral Therapy Era in Johannesburg, South Africa. (1st November 2021) - Wiggill, Tracey; Mayne, Elizabeth; Perner, Yvonne; Vaughan, Jenifer
Abstract : Background: South Africa has a high HIV prevalence, which associates with an increased risk of lymphoma. Antiretroviral therapy (ART) became accessible in 2004, but the program has substantially expanded. Changes in lymphoma patterns are documented in high-income countries after wide-scale ART including declining high-grade B-cell non-Hodgkin lymphomas (HG B-NHLs), particularly diffuse large B-cell lymphoma, and increased Hodgkin lymphoma (HL). There are limited data from Africa. This study aimed to compare HG B-NHL characteristics in the early (2007) and later (2017) ART era. Methods: All incident lymphomas at the National Health Laboratory Service, Johannesburg, were identified using the laboratory information system, and data were collected for each patient. Results: The total number of lymphoma cases increased from 397 (2007) to 582 (2017). This was associated with improved lymphoma classification and patient referral for oncological care. HG B-NHL remained the most diagnosed lymphoma subtype in 2017 comprising 70% of HIV-associated lymphomas, followed by HL (24%). Diffuse large B-cell lymphoma comprised 65% of all HG B-NHLs and 45% of all lymphomas in people with HIV in 2017. Significantly more patients were on ART in 2017, with improvements in virological control documented. Despite this, 47.6% of patients were not virologically suppressed, and 37.5% of patients were ART-naive at time of diagnosis in 2017. Immunological reconstitution was suboptimal, which may reflect late initiation of ART. Conclusion: Public health initiatives to initiate ART as early as possible and to retain patients in ART programs may assist in decreasing the number of HIV-associated lymphomas in our setting. Abstract : Supplemental Digital Content is Available in the Text.